Joint phy/mac layer security design using arq with mrc and null-space independent papr-aware artificial noise in siso systems - Hamamreh, Jehad M.; Arslan, Hüseyin (IEEE-Institute of Electrical and Electronics Engineers Inc, 2018)
Automatic-repeat-request (ARQ) as a MAC layer mechanism and artificial noise (AN) as a physical layer mechanism along with the help of maximal ratio combining (MRC), are jointly designed to achieve secrecy. Basically, a special AN, which does not require null-space in the channel, is designed based on the quality of service requirements and the channel condition between the legitimate parties and injected to the data packet. If the same packet is requested by the legitimate receiver (Bob), an AN canceling signal is properly designed and added to the next packet. Then, an AN-free packet is obtained by using MRC process at Bob, while deteriorating the eavesdropper's performance. Furthermore, two simple closed-form expressions of the achievable secure throughput are derived. The first one is given in a closed-form for the case of ARQ scheme without AN, while the second one is given in an upper-bound form for the case of ARQ with AN. Moreover, this paper addresses two critical security-associated problems: 1) the joint design of secrecy, reliability, throughput, delay and the tradeoff among them, and 2) the increase in the peak-to-average power ratio (PAPR) due to the added AN. Finally, the proposed design is extended to OFDM to demonstrate its capability in not only enhancing the secrecy due to the frequency selectivity of the channel, but also in reducing the PAPR and out-of-band emission of OFDM-based waveforms, while maintaining secrecy.
WOS: 000444652500038
Keywords: Cross PHY/MAC Layer Security; Automatic Repeat Request (ARQ); Peak-to-Average Power Ratio (PAPR); Out-off-Band Emission (OOBE); Artificial Noise (AN); Maximum Ratio Combining (MRC); Quality of Service (QoS); Throughput; Secure Throughput; Delay; Perfect Secrecy; Packet Error Rate (PER)